Firmware protocol stack supporting remote boot and storage volumes mapping in IP-SAN - TAN Huai-liang; YIN Bin (Tongxin xuebao)
A new remote boot technology based on IP storage area network was designed, and the core technology of it is the firmware protocol stack running under bare machine platform. A non-routing iSCSI/TCP protocol prototype was proposed and implemented based on firmware.At the same time, several optimization algorithms were introduced to enhance the performance and reliability of remote boot, including optimistic forecast, fixed avoiding retransmit algorithm and output request suspend strategy that solved the problem of reentry. A firmware iSCSI initiator finite state machine model was established which can be easily taken over by kernel mode initiator. Then the firmware protocol stack was integrated into IP-SAN extension BIOS, applied to client host with no local storage devices, and achieves network boot based on IP-SAN. Test results show it has very good performance and reliabrity. Deployment,movement and re-distribution of relations between host and storages become more easily.